Asuhan Keperawatan Anak Pada Pasien Dengan Morbili Di Ruang Marwa Di Rumah Sakit Aisyiyah Pariaman Tahun 2026 - Mayang Aprilliona; Reska Handayani; Prima Yoselina; Yessy Aprihatin (CV. ITTC INDONESIA, 2026)
Morbili is a highly contagious acute viral infection and remains a health problem, especially in children. The number of morbili cases recorded in the Marwa Ward of Aisyiyah Pariaman Hospital is increasing, namely 5 cases in 2023, 1 case in 2024, and increasing to 58 cases in 2025. Morbili is also included in the three most common diseases and has caused extraordinary events (KLB). This condition requires optimal care. The high frequency of occurrence and the danger of life threatening complications require effective and comprehensive treatment. This condition requires the provision of comprehensive and targeted care to prevent complications. This study aims to provide an overview of the nursing care process including assessment, diagnosis, planning, implementation, and evaluation in children with morbili. This study was conducted using a case study method from February 10 to 14, 2026, in the Marwa Ward of Aisyiyah Pariaman Hospital. The results revealed health problems such as ineffective airway clearance, hyperthermia, diarrhea, and the risk of nutritional deficits. Interventions included monitoring vital signs, regular temperature monitoring, maintaining the airway, and meeting fluid needs to prevent dehydration. Five days after surgical intervention, secretions were removed, the child's temperature returned to normal, diarrhea frequency decreased, and appetite improved. Appropriate care can stabilize the condition of children with Morbili and can serve as a reference for implementing pediatric care practices.